Toni Morrison’s paradise: the unreliable narrator - Mansouri, Shahriyar; Omar, Noritah (Universiti Putra Malaysia Press, 2010)
Previous critical readings of Toni Morrison’s novels, especially Paradise, largely emphasise the universal themes explored in her novels, namely, feminism, culture, psychology, and of course, her remarkable presentation of African-Americans in racial and cultural conflicts. Yet, there are major areas that remain unexplored in her works. One of the most conspicuous absences is Morrison’s dominance over the art of narration. Narratology, as a science, studies the ways in which narration and narrators help us shape our perceptions of reality, cultural artifacts, clichés, etc. Needless to say, it is Morrison’s ceaseless dominance and control over the art of narration that take her novels, including Paradise, to a new level and style - a modern style, which Roland Barthes refers to as the “writerly text.” By setting the science of narration as the cornerstone of this paper, the following notions will receive a proper narratological definition: (a) how the various stories, initially narrated by unrelated characters are juxtaposed against each other to convey a single plot/storyline, and (b) how a singular omniscient/omnipresent narrator is unable to lead the narrative towards a satisfactory ending. In order to investigate the significance of utilising a labyrinthine narrative form in modern texts, this paper studies the variety and relevance of the employed forms of narration, through the interdisciplinary science of narratology.